Guidelines of education administration based on agricultural technology innovation for Guangxi higher vocational colleges - Xiao Shalang,; Patchara Dechhome,; Niran Sutheeniran,; Sarayuth Sethakhajorn, (Utilitas Mathematica, 2025)
The objectives of this research were: 1) to study the current situation of education administration based on agricultural technology innovation for Guangxi higher vocational colleges. 2) to provide the guidelines of education administration based on agricultural technology innovation for Guangxi higher vocational colleges. 3) to evaluate the suitability and feasibility of guidelines of education administration based on agricultural technology innovation for Guangxi higher vocational colleges. The population were 369 research administrators from 6 agricultural higher vocational colleges in Guangxi. Research instruments include: 1) questionnaire, 2) structured interview, and 3) evaluation form. Data analysis were by using percentage, mean, standard deviation and content analysis. The results were found that the current situation of education administration based on agricultural technology innovation for Guangxi higher vocational colleges in six aspects was at a medium level. Considering the results of this research aspects ranged from the highest to lowest mean were as follow: the highest mean was demand for vocational and technical talents, followed by both knowledge acquisition ability and income, both knowledge coupling ability and knowledge application ability were the lowest mean. There were 48 guidelines for education administration based on agricultural technology innovation for Guangxi higher vocational colleges in six aspects. The results about evaluation of the suitability and feasibility of guidelines for education administration based on agricultural technology innovation of Guangxi higher vocational colleges was at highest level.